Perancangan Desain Interaksi Aplikasi Info Wisata Kota Malang Modul Info Wisata dengan Metode Competitive Analysis - Angelin Anggraeni Misi; Herman Tolle; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Services in the form of delivering tourist information are being pursued by the Malang City Government. Malang City tourism management is handled by the Malang City Youth, Sports and Tourism Office. The number of visits in 2018 foreign tourists around 15,304, Indonesian tourists around 4.8 million. DISPORA Malang City strives to disseminate tourism information efficiently and effectively, so that it can support Malang City to become a smart city. One of the efforts is to design a tourist info application for Malang City based on mobile apps, by adjusting user needs and being integrated with local offices. This study uses the Human - Centered Design method, understands and analyzes the user context, analyzes user needs using the Competitive Analysis method from the point of view of strength, weakness, content, design, user experience, and opportunity, which results in design suggestions for application design. Making design solutions in the form of wireframes, mockups, and high fidelity prototypes. The prototype testing phase used 15 respondents. In testing there are six task scenarios, to get results from the effective, efficient, and user satisfaction aspects using the System Usability Scale (SUS) questionnaire. The results of the effective aspect are 96.6%, efficiency aspects are 91.8%, user satisfaction aspects are 77.3%, the prototype is on a grade scale C which is 71 - 83, acceptability ranges are acceptable, and adjective ratings are good. an average of 88.5%.